Obesity-Induced Changes in Adipose Tissue Microenvironment and Their Impact on Cardiovascular Disease. Issue 11 (27th May 2016) - Fuster, José J.; Ouchi, Noriyuki; Gokce, Noyan; Walsh, Kenneth
Abstract : Obesity is causally linked with the development of cardiovascular disorders. Accumulating evidence indicates that cardiovascular disease is the collateral damage of obesity-driven adipose tissue dysfunction that promotes a chronic inflammatory state within the organism. Adipose tissues secrete bioactive substances, referred to as adipokines, which largely function as modulators of inflammation. The microenvironment of adipose tissue will affect the adipokine secretome, having actions on remote tissues. Obesity typically leads to the upregulation of proinflammatory adipokines and the downregulation of anti-inflammatory adipokines, thereby contributing to the pathogenesis of cardiovascular diseases. In this review, we focus on the microenvironment of adipose tissue and how it influences cardiovascular disorders, including atherosclerosis and ischemic heart diseases, through the systemic actions of adipokines.